2007
DOI: 10.1016/j.physbeh.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Neural network interactions and ingestive behavior control during anorexia

Abstract: Many models have been proposed over the years to explain how motivated feeding behavior is controlled. One of the most compelling is based on the original concepts of Eliot Stellar whereby sets of interosensory and exterosensory inputs converge on a hypothalamic control network that can either stimulate or inhibit feeding. These inputs arise from information originating in the blood, the viscera, and the telencephalon. In this manner the relative strengths of the hypothalamic stimulatory and inhibitory network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
(51 reference statements)
3
23
0
Order By: Relevance
“…Deep brain stimulation of the mammillary bodies and the mammillothalamic tract are currently being investigated as potential treatments for seizure control (van Rijckevorsel et al, 2005;Khan et al, 2009). The paraventricular nucleus of the hypothalamus is a complex motor relay, integrating essential endocrine and autonomic responses that sustain homeostasis (Thompson and Swanson, 2003;Watts et al, 2007). Neuroanatomical studies have reported alterations in the cytoarchitecture of this nucleus in patients with homeostatic control deficits, such as Prader-Willi syndrome, diabetes insipidus, depression and AIDS (Swaab et al, 1993;Swaab, 1995;Overeem et al, 2002;Swaab, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Deep brain stimulation of the mammillary bodies and the mammillothalamic tract are currently being investigated as potential treatments for seizure control (van Rijckevorsel et al, 2005;Khan et al, 2009). The paraventricular nucleus of the hypothalamus is a complex motor relay, integrating essential endocrine and autonomic responses that sustain homeostasis (Thompson and Swanson, 2003;Watts et al, 2007). Neuroanatomical studies have reported alterations in the cytoarchitecture of this nucleus in patients with homeostatic control deficits, such as Prader-Willi syndrome, diabetes insipidus, depression and AIDS (Swaab et al, 1993;Swaab, 1995;Overeem et al, 2002;Swaab, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the paraventricular nucleus of the hypothalamus (PVH) contains neurons that comprise the "behavior controller" for feeding. The integrated output from the feeding behavior controller then regulates the downstream motor network that ultimately controls motor neurons in the hindbrain and spinal cord responsible for executing feeding behavior (39,41,54). This model further posits that different types of feeding use distinct sets of afferents from other parts of the hypothalamus (particularly the ARH), the telencephalon, and hindbrain to engage motivated feeding behavior controllers in the PVH and possibly the lateral hypothalamic area (LHA) (54).…”
mentioning
confidence: 99%
“…The integrated output from the feeding behavior controller then regulates the downstream motor network that ultimately controls motor neurons in the hindbrain and spinal cord responsible for executing feeding behavior (39,41,54). This model further posits that different types of feeding use distinct sets of afferents from other parts of the hypothalamus (particularly the ARH), the telencephalon, and hindbrain to engage motivated feeding behavior controllers in the PVH and possibly the lateral hypothalamic area (LHA) (54). For example, 2-DG-stimulated feeding requires ascending catecholaminergic afferents from the hindbrain but not neurons in the mediobasal hypothalamus (MBH) (3,24,26), whereas the feeding effects of interocerebroventricular (icv) injections of leptin and ghrelin are severely compromised by lesions of MBH neurons (3).…”
mentioning
confidence: 99%
“…It has been previously described that c-fos expression is not activated in LHA orexinergic cells in DIA paradigm (Watts et al, 2007). Furthermore, non-responding orexinergic neurons have been observed in animals where an anorexic behavior is induced by a LPS injection (Becskei et al, 2008).…”
Section: Tshmentioning
confidence: 95%
“…Analysis of the expression of feeding-regulating peptides in the ARC of males after 5 days has shown a decreased synthesis of POMC and increased NPY mRNA levels (Watts et al, 1999), which have anorexigenic and orexigenic effects, respectively. All those changes are signals that should be increasing appetite and food ingestion in animals, however feeding is suppressed in dehydrated rats, which suggests that inhibitory control networks, other than those of the ARC, are activated (Watts, 2001(Watts, , 2007.…”
Section: Dehydration-induced Anorexiamentioning
confidence: 99%